Suture-Free and Mesh Reinforced Small Intestinal Anstomoses: A Feasibility Study in Rabbits. (1st August 2013) - Ulmer, T. F.; Stumpf, M.; Rosch, R.; Junge, K.; Binnebösel, M.; Trotha, K. T. von; Oettinger, A. P.; Neumann, U.
ABSTRACT: Introduction : Anastomotic leakage still remains a major complication in general surgery. Beside general risk factors, the ideal method of anastomotic technique has not been found until now. The aim of the present study was to analyze wound healing in suture-free small intestine anastomoses using fibrin glue with and without mesh-reinforcement. Methods : Laparotomy and four different types of small bowel anastomoses were performed in 32 chinchilla rabbits. Standard hand-sewn anastomoses (CG), suture-free glued anastomoses (FG) with and without mesh reinforcement using two different types of meshes [Vicryl-mesh (VM) and Surgisis (SM)]. Animals were sacrificed after 5 and 21 days. Bursting pressure, collagen type I/III ratio, and matrix-metalloproteinase 2, 9, and 13 were analyzed. Results : None of the animals died due to an anastomotic leakage. All animals in the long term group with Surgisis mesh died due to a mechanical bowel obstruction based on a distinctive stenosis of the anastomosis. The bursting pressures did significantly differed in animals with fibrin glue alone compared to animals with Vicryl-mesh reinforcement ( p < 0.05). Histological examination revealed statistically significant differences ( p < 0.05) in the values for MMP-2 (VM < SM), MMP-9 (VM < CG), and MMP-13 (CG < SM, VM < FG, and VM < SM). However, collagen type I/III ratios were not significantly different between groups. Conclusions : Our results suggest that a mesh reinforced glued anastomosis is technically feasible. Furthermore, mesh-reinforcement using VM increased the integrity and simplified the technique of suture-free anastomoses.